Culture, Ethnic, Lifestyle, and Diabetes - Windy Tri Yuana; Sri Widati; Oedojo Sudirham (Indian Journal of Forensic Medicine & Toxicology, 2021)
Diabetes is a social health problem that is large with special attention in the community and amongindividuals. Nevertheless, the efforts to spread paradigm of health society to inputsocial determinant ofhealth including analysis and contextual of social factors that are considered out of the scope of the healthresearch is seldom conducted. As a result, the conceptualization of dynamic health inequality of diabetesis superficial. By using a holistic anthropologist lens has the potency to offer insight intothe character ofsocialdeterminer which is wider. The individual factor that is traditionally focused on the health of society andqualitative exploration structural, deeply local context, social environment, and culture, and their interactionand intersexuality, as the key factors, while considering how to reach alterations. The systematic study aimsto describe that culture, ethnicity, and lifestyle have much impacton the patients of diabetes mellitus. Themethod of the systematic study is the article’s investigations which are listed by PubMed with the keywords“culture, ethnic, lifestyle, and diabetes”. Twenty-nine articles are got from the result of an investigation andafter a selection has been done and got five articles to be analyzed furthermore. The result of the review ofthe literature study shows that culture, ethnicity, and lifestyle are able to influence the case of diabetes illnessto the individual or group. On a certain ethnic group besides economic problem, the characteristic ofcertainbody starts from size and shape of the body make someone can suffer from diabetes, in addition,the motoricactivity of the body and physical activity can influence the case of diabetes.